Incidence of atrial functional tricuspid regurgitation and its correlation with tricuspid valvular deformation in patients with persistent atrial fibrillation - Yamamoto, Yuko; Daimon, Masao; Nakanishi, Koki; Nakao, Tomoko; Hirokawa, Megumi; Ishiwata, Jumpei; Kiriyama, Hiroyuki; Yoshida, Yuriko; Iwama, Kentaro; Hirose, Kazutoshi; Mukai, Yasuhiro; Takeda, Norifumi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: With the growing prevalence of atrial fibrillation (AF), concomitant atrial functional tricuspid regurgitation (FTR) is increasing. In this study, we aimed to elucidate the incidence of significant atrial FTR and its association with tricuspid valvular (TV) deformation in patients with persistent AF. Methods: We retrospectively enrolled 344 patients (73.0±9.3 years, 95 female) with persistent AF who underwent 2-dimensional echocardiography. We excluded patients with left-sided heart disease, pulmonary hypertension treated with pulmonary vasodilators, and congenital heart disease. We defined significant TR as having TR ≥ moderate; and tricuspid annulus (TA) diameter, tethering height, and area were measured in all patients. Results: Among the study population, 80 (23.3%) patients had significant TR. TA diameter, tethering height, and area were significantly greater in the significant TR group (all p<0.001). In multivariable analysis, TA diameter was independently associated with significant TR (odds ratio 1.1 per mm, p=0.03), whereas TV tethering height was not. Receiver operating characteristic curve for significant TR exhibited the best predictive value of TA diameter indexed for body surface area (23 mm/m2; area under the curve [AUC] = 0.87) compared with absolute TA diameter (39 mm; AUC = 0.74) and TA diameter indexed for height (0.22 mm/cm; AUC = 0.80). Conclusions: Approximately 25% of patients with persistent AF had significant TR. The BSA-corrected TA diameter was strongly associated with significant TR, which might be helpful for predicting the development of significant TR and considering its therapeutic strategy in patients with persistent AF.